Pengaruh Financial Distress Model Altman Z-Score terhadap Harga Saham pada Perusahaan Ritel di Indonesia - Nurul Hidayanita; Meliza Zafrizal (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The number of retail companies in Indonesia tends to decrease, especially during the Covid-19 Pandemic. This decrease was caused by increasing financial distress which led to bankruptcy. Financial distress is one of the causes of a decline in financial performance and ultimately leads to bankruptcy. Therefore, this study examines the impact of financial distress on stock prices at retail companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021. Financial distress as independent variable is measured by the Altman Z-score method. On the other hand, the dependent variable of this study is stock prices. Panel data regression using a random-effect model is applied to test the effect of financial distress on stock prices. The results of the analysis show that WCTA and MVEBVTL have no significant impact on stock prices. Meanwhile, RETA, EBITTA, and STA have a positive and significant impact on stock prices.